Effects of long-term testosterone treatment on cardiovascular outcomes in men with hypogonadism: Rationale and design of the TRAVERSE study - Bhasin, Shalender; Lincoff, A. Michael; Basaria, Shehzad; Bauer, Douglas C.; Boden, William E.; Cunningham, Glenn R.; Davey, Deborah; Dubcenco, Elena; Fukumoto, Sandra; Garcia, Michelle; Granger, Christopher B.; Kalahasti, Vidyasagar; et al. (The American heart journal, 2022)
Testosterone exerts some effects on the cardiovascular system that could be considered beneficial; some other effects may potentially increase the risk of cardiovascular (CV) events. Neither the long-term efficacy nor safety of testosterone treatment has been studied in an adequately-powered randomized trial. The Testosterone Replacement therapy for Assessment of long-term Vascular Events and efficacy ResponSE in hypogonadal men (TRAVERSE) study is a randomized, double-blind, placebo-controlled, parallel group, non-inferiority, multicenter study. Eligible participants are men, 45 to 80 years, with serum testosterone concentration <300 ng/dL and hypogonadal symptoms, who have evidence pre-existing CV disease or increased risk of CV disease. Approximately 6,000 subjects will be randomized to either 1.62% transdermal testosterone gel or a matching placebo gel daily for an anticipated duration of up to 5 years. The primary outcome is CV safety defined by the major adverse CV event composite of nonfatal myocardial infarction, nonfatal stroke, or death due to CV causes. The trial will continue until at least 256 adjudicated major adverse CV event endpoints have occurred to assess whether the 95% (2-sided) upper confidence limit for a hazard ratio of 1.5 can be ruled out. Secondary endpoints include prostate safety defined as the incidence of adjudicated high grade prostate cancer and efficacy in domains of sexual function, bone fractures, depression, anemia, and diabetes. As of July 1, 2021, 5,076 subjects had been randomized. The TRAVERSE study will determine the CV safety and long-term efficacy of testosterone treatment in middle-aged and older men with hypogonadism with or at increased risk of CV disease.